Pendayagunaan Zakat Produktif: Solusi Dalam Memberantas Kemiskinan Umat (Studi Pada Lapak Berkah Binaan IZI Makassar) - Sudirman; Muhammad Nasri Katman; Alimuddin; Darwis Said; Muhammad Febriansyah (LAA MAISYIR: Jurnal Ekonomi Islam, 2025)
This study aims to analyze the model of productive zakat utilization implemented by the Indonesian Zakat Initiative Makassar in empowering the economic capacity of mustahiq within the Lapak Berkah group. The study employs a qualitative approach using a case study method. Data were collected through in depth interviews with program managers, facilitators, and mustahiq, complemented by field observations and a review of relevant program documentation. Data analysis was conducted qualitatively through an iterative and continuous process involving data reduction, data display, and conclusion drawing. The findings indicate that the utilization of productive zakat by IZI Makassar is implemented through a series of systematic stages, including the assessment of prospective mustahiq, the phased distribution of business capital assistance, business mentoring and entrepreneurship training, monitoring and evaluation of business development, and religious guidance. Qualitatively, this utilization model is considered effective in enhancing the economic capacity of mustahiq, as reflected in positive developments in business performance, increased turnover, expansion of marketing networks, strengthening of working capital, and heightened awareness as well as capacity to contribute infaq. These findings affirm that productive zakat has significant potential as an instrument for community economic empowerment. However, its effectiveness is highly contingent upon the quality of mentoring, program sustainability, and the readiness of mustahiq to manage their businesses independently.